The Role of Reading in Russian Language Lessons - Касимова Камила Махаммаджоновна (Scientific Trends, 2024)
This article discusses the process of reading as an important link in teaching Russian as a foreign language. The Role and Tasks of Reading Types in Russian Language Lessons.
Keywords: Semantic reading, introductory reading, learning reading.